Reversal in fatigued athletes of a defect in interferon secretion after administration of Lactobacillus acidophilus - Clancy, R. L.; Gleeson, M.; Cox, A.; Callister, R.; Dorrington, M.; D`Este, C.; Pang, G.; Pyne, D.; Fricker, P.; Henriksson, A. (British Journal of Sports Medicine, 2006)
Background: Fatigue and impaired performance in athletes is well recognised and has been loosely linked to "overtraining". Reduced concentration of IgA in the saliva and increased shedding of Epstein Barr virus (EBV) have been associated with intense training in elite athletes.